Viability assessment of electric cars for personal use in India. (July 2022) - Jain, Deepty
Abstract: The study assesses the viability of electric cars for personal use in India based on the driving range and travel pattern, vehicle ownership and income levels and energy demand. The study estimates the expected personal electric car stock in India using a scenario-based approach. This is used to further estimate the electricity demand. Growing income levels present a potential for converting personal cars to electric, however, the limited percentage of multicar households in India limits its viability. The analysis shows that the low powertrain models can meet most of the daily travel demand in a single charge. However, the increasing ownership of large-size vehicles and growing travel distances impose a burden on electricity demand. There is a need to adopt a package of policies to restrain the growing vehicle ownership, retain the existing travel intensity and manage the energy demand. Highlights: Assess viability of personal electric cars related to travel needs, energy demand and vehicle ownership using 27 scenarios. The existing low powertrain models can meet daily travel demand in a single charge. Additional power demand to charge electric cars can be reduced by encouraging low powertrain models. Based on the existing vehicle ownership pattern, low EV scenario is viable in India. Travel demand and energy management strategies required to enable electric cars sustainability in India.